Effect of Insecticidal Seed Treatment on Storability of Pearl millet Seed - GM BANSODE; UK KADAM; VR SHELAR (Seed Research, 2026)
A study was conducted to assess the effect of new insecticides on lesser grain borer, Rhyzopertha dominica infesting stored pearl millet seed at MPKV, Rahuri, Maharashtra during 2013-14. The results revealed that the seed treatment of deltamethrin 2.8 EC @ 1ppm (0.04 ml/kg seed) or spinosad 45 SC @ 2ppm (4.4mg/ kg seed) or emamectin benzoate 5SG @2ppm (40 mg/kg seed) were equally effective for control of storage insect, R. dominica and for maintaining the pearl millet seed germination above minimum seed certification standard (75%) up to 9 months of storage.